2021
DOI: 10.1126/sciadv.abf7293
|View full text |Cite
|
Sign up to set email alerts
|

Observation of cavitation governing fracture in glasses

Abstract: Crack propagation is the major vehicle for material failure, but the mechanisms by which cracks propagate remain longstanding riddles, especially for glassy materials with a long-range disordered atomic structure. Recently, cavitation was proposed as an underlying mechanism governing the fracture of glasses, but experimental determination of the cavitation behavior of fracture is still lacking. Here, we present unambiguous experimental evidence to firmly establish the cavitation mechanism in the fracture of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 61 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…Unlike crystalline alloys, the plastic deformation of MGs is highly localized into nanoscale shear bands, which is prone to become runaway with the assistance of strain softening [10,11]. As a result, MGs display a propensity for catastrophic and instantaneous brittle failure [12], which has become the Achilles' heel for their structural applications. Over the past decades, significant efforts have improved the deformability of MGs, mostly focusing on uniformly distributing shear bands via introducing secondary phases or structural inhomogeneities into glassy matrix or hindering the propagation of a single shear band [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike crystalline alloys, the plastic deformation of MGs is highly localized into nanoscale shear bands, which is prone to become runaway with the assistance of strain softening [10,11]. As a result, MGs display a propensity for catastrophic and instantaneous brittle failure [12], which has become the Achilles' heel for their structural applications. Over the past decades, significant efforts have improved the deformability of MGs, mostly focusing on uniformly distributing shear bands via introducing secondary phases or structural inhomogeneities into glassy matrix or hindering the propagation of a single shear band [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there is an increased interest in the phenomenon given its significance in the context of failure of amorphous solids via crack propagation [9][10][11]. Recent experiments have clearly demonstrated that emergence of isolated cavities and subsequent merger of these micro-cavities eventually leads to complete failure via fracture [12]. Further, cavitation is often cited as the source of damages in soft disordered solids like biological tissues [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether or not this well-known property is also observed on the micro-and meso-scale has been controversial for decades, as documented in several review articles [11][12][13]. One of the questions that is highly debated is whether or not the fracture of oxide glasses is accompanied by the formation, growth and coalescence of microscopic cavities in front of the crack tip [14][15][16][17][18][19][20][21][22][23], features that are usually associated with ductile fracture. In experiments glass fracture is frequently investigated by means of atomic force microscopy (AFM), often in a stress-corrosive environment, i.e., when water interacts with the glass structure [24].…”
Section: Introductionmentioning
confidence: 99%